Evidence of the relationship between budgetary participation, organizational commitment and managerial performance - Guidini, Andreia Acássia; Zonatto, Vinicius Costa da Silva; Degenhart, Larissa (Revista de Administração da UFSM, 2020)
Purpose – This research objective to investigate the relations between budgetary participation, organizational commitment and managerial performance. Design/methodology/approach – A descriptive, survey and quantitative study was carried out, based on trajectory analysis and with data from 150 managers with budgetary responsibilities of the largest Brazilian export companies in the business. Findings – The results reveal that budgetary participation influences managerial performance in two ways: directly, as a result of managers 'involvement and influence in the budgeting process, and indirectly, when managers' commitment to the organization increases due to their participation and involvement in budgetary definitions. Research limitations/implications – The limitation of the use of self-reported measures to measure the proposed relationships is highlighted. This research indicates that behavioral aspects related to the budgeting process, have significant implications for work-related results. Practical implications – The results suggest that organizations should allow the participation of managers in setting goals and budget objectives, as this action triggers a greater commitment of the individual to the organization and better performance in the work. Social implications – The findings can help organizations to understand factors that can be improved in the organization so that employees feel committed to the company in which they operate and consequently present better budgetary participation and performance. Originality/value – This research sought to expand the existing discussion in the accounting literature on the role of budgetary processes and their implications for organizational commitment and managerial performance in budgetary activities.